Faktor Dominan Risiko Terjadinya Penyakit Jantung Koroner (PJK) - Ros Endah Happy Patriyani; David Ferry Purwanto (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Risk Factors, CHD. Coronary Heart Disease (CHD) is the coronary atherosclerotic disease that causes narrowing of blood vessels. Constriction of blood vessels occurs because of atherosclerosis or spasm or a combination of both. the risk factors of CHD were divided into two, namely the factors that can not be changed and the factors can be changed. Factors that can not be changed include age, family history and gender. While the factors that can be changed include an increase in serum lipids (hyperlipidemia), personality type, smoking, impaired glucose tolerance (diabetes mellitus), lifestyle is less activity (physical inactivity), psychological stress, and hypertension. The purpose of this study to determine the risk factors that lead to increased incidence of coronary heart disease. The study is an observational analytic epidemiologic approach with cross sectional design with a sample of 40 respondents. The data analysis using logistic regression. The results showed the significant influence of CHD events by a factor of age> 40 years (p = 0.7370, hyperlipidemia (p = 0162), hypertension (p = 0365), smoking (p = 0153), as well as physical inactivity (p = 0535 ). Smoking is a risk factor most dominant effect on the incidence of CHD with OR = 4,500. the case studies are necessary to further research with a number of larger samples and develop variable-varabel to be studied is associated with other behaviors and lifestyles that affect developing CHD.